Phase equilibrium data and modeling of ethylic biodiesel, with application to a non-edible vegetable oil. (1st September 2017) - Muhammad, Fahad; Oliveira, Mariana B.; Pignat, Patrice; Jaubert, Jean-Noël; Pinho, Simão P.; Coniglio, Lucie
Abstract: Contributing to extending the knowledge for the design and operation of biodiesel production processes, isobaric PTxy vapor-liquid equilibria data of ethanol + ethyl hexanoate, 1-pentanol + ethyl hexanoate and 1-pentanol + ethyl octanoate at two different pressures are reported for the first time. Consistency tests were applied to attest the quality of the collected data, for these especially complex measurements. Besides that, vapor pressures of the pure ethyl esters have also been measured. For modeling purposes, the Lyngby and Dortmund UNIFAC variants were used to predict the VLE phase diagrams. Generally, the predictions are of very good quality, being the UNIFAC-Do (Dortmund) better, as the deviations in temperature and vapor compositions are always lower to 1.0 K and 0.020, respectively. Checking for the viability for extrapolations in pressure, CPA EoS was also applied to the modeling of the experimental data with very good results. Finally, aiming at examining the model capabilities to describe multicomponent systems, VLE measurements involving two alcohols and the fatty acid ethyl ester mixture obtained from non-edible vegetable oil have been carried out showing the good performance of the predictive models.